Seizures and Consciousness Disorder Secondary to Intracranial Hypotension After Spinal Surgery: A Case Report and Literature Review - Lv, Yuqing; Xiang, Hui (Frontiers in Neurology, 2022)
Patient concerns: A 72-year-old Chinese male patient developed status epilepticus, disorder of consciousness, and quadriplegia when he finished spinal surgery. While he had no previous seizures, nor any seizure risk factors. Diagnosis: After MRI and CT examination, combined with the clinical manifestations of the patient, intracranial hypotension due to cerebrospinal fluid leakage was diagnosed. Interventions: In the early stage, we carried out strict perioperative critical care for the patient. Trendelenburg position was conducted to relieve intracranial hypotension. The dural repair surgery was performed after diagnosis of CSF leakage. Traditional Chinese acupuncture and massage therapy also offered significant benefits in the rehabilitation process. Outcomes: Seizures in the patient were cured. Three months after discharge, he was gradually returning to normal life. Lessons: Unexplained seizures and disorder of consciousness after spinal surgery may be highly suggestive of the presence of a cerebrospinal fluid leakage associated with intracranial hypotension syndrome. Trendelenburg position and dural repair surgery are effective ways to relieve intracranial hypotension and associated symptoms. Better awareness of the association between IH (intracranial hypotension) and SE (status epilepticus) may help us improve early recognition of the syndrome.